2016
DOI: 10.1038/srep38311
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker MicroRNAs for Diagnosis, Prognosis and Treatment of Hepatocellular Carcinoma: A Functional Survey and Comparison

Abstract: Hepatocellular Carcinoma (HCC) is one of the most common malignant tumors with high incidence and mortality rate. Precision and effective biomarkers are therefore urgently needed for the early diagnosis and prognostic estimation. MicroRNAs (miRNAs) are important regulators which play functions in various cellular processes and biological activities. Accumulating evidence indicated that the abnormal expression of miRNAs are closely associated with HCC initiation and progression. Recently, many biomarker miRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 142 publications
(226 reference statements)
0
60
1
Order By: Relevance
“…A number of studies have emerged revealing that miRNAs are aberrantly expressed in HCC (35)(36)(37). Changes in miRNA expression have been continuously reported to serve as the main drivers of HCC carcinogenesis and development by regulating a variety of cancer-associated biological processes (22).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have emerged revealing that miRNAs are aberrantly expressed in HCC (35)(36)(37). Changes in miRNA expression have been continuously reported to serve as the main drivers of HCC carcinogenesis and development by regulating a variety of cancer-associated biological processes (22).…”
Section: Discussionmentioning
confidence: 99%
“…10 Increasing numbers of reports have revealed that many miRNAs are aberrantly expressed in HCC and have indicated the involvement of miRNAs in hepatocarcinogenesis including progression to later stages of liver cancer. [11][12][13] A growing body of experimental evidence suggests that miRNAs can exert oncogenic or tumor-suppressive actions in HCC and can regulate a wide range of biological phenomena, such as cell proliferation, apoptosis, cell cycle, metastasis, epithelial-mesenchymal transition, and chemoresistance. [14][15][16] Thus, miRNAs may be promising targets for noninvasive treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous miRNAs in HCC have been widely investigated, and have also been identified as diagnostic and prognostic markers as well as therapeutic candidates for HCC. This strategy may provide accurate clinical decisions for HCC diagnosis and treatment (19,20).…”
Section: Introductionmentioning
confidence: 99%